2022
DOI: 10.3389/fmed.2022.877213
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity/Spirituality and Mental Health in Older Adults: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: ObjectivesThe present study investigated the association between religious and spiritual (RS) practices with the prevalence, severity, and incidence of mental health problems in older adults.MethodsWe conducted a systematic review and meta-analysis of cross-sectional and longitudinal studies that investigated older adults aged 60+ years and assessed RS using valid scales and questions from valid scales, and mental health according to validated multidimensional or specific instruments. Studies were retrieved fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 179 publications
0
8
0
Order By: Relevance
“…A key component of successful aging, lifestyle factors such as religious and spiritual practices may reduce the risk of cognitive impairment and improve mental and physical health ( Balboni et al 2022 ; Coelho-Junior et al 2022 ; Paillard-Borg et al 2009 ) but more research is needed examining associations with dementia progression using a larger sample size. Most published studies have looked at prayer among adults with advanced illness and dementia caregivers but there is a large gap among persons with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…A key component of successful aging, lifestyle factors such as religious and spiritual practices may reduce the risk of cognitive impairment and improve mental and physical health ( Balboni et al 2022 ; Coelho-Junior et al 2022 ; Paillard-Borg et al 2009 ) but more research is needed examining associations with dementia progression using a larger sample size. Most published studies have looked at prayer among adults with advanced illness and dementia caregivers but there is a large gap among persons with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…26 The GDS contains 30 items that are answered using a "yes/no" format. The total score ranges from 0 to 30, the individuals are categorized into three groups using the cut-off point: normal (0-9); mild depressives (10)(11)(12)(13)(14)(15)(16)(17)(18)(19); severe depressives (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The GDS has good reliability and validity in Chinese older adults.…”
Section: Depressive Symptommentioning
confidence: 99%
“…13 A recent systematic review found that individuals with high spirituality had a lower prevalence of depressive symptoms. 14 And it was associated with a reduced incidence risk of depressive symptoms among older adults with heart failure and/or chronic pulmonary disease. 15 In addition, individuals with high level of spirituality also have a significantly increased rate of depression remission over time among the patients with depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this model comprises four dimensions: physical, cognitive, social, and spiritual [ 12 ]. Spirituality/religion is related to the personal meaning of life and its relationship to a supreme being, and although it is a complex construct, spirituality seems to be related to healthy aging behaviors, such as self-care [ 13 ]. On the other hand, in recent years, a new approach to healthy aging postulates that personal development in old age is possible [ 14 ].…”
Section: Introductionmentioning
confidence: 99%